1998
DOI: 10.2134/jeq1998.00472425002700030020x
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Growth and Trace Metal Accumulation on Metalliferous Wastes

Abstract: A greenhouse study was conducted to investigate the growth of the grass cover crops Agrostis capillaris, Festuca ovina, F. rubra, Lolium perenne, and Phleum pratense and their accumulation of Cu, Pb, Zn, Ni, and Cr in three metal‐contaminated wastes arising from a steelworks, a lead mine, and a chemical works. Soil metals were extracted by five reagents (Mehlich 1, 0.1 M HCl, 0.005 M DTPA, 0.005 M EDTA, 0.005 M NTA) and values were correlated with plant tissue accumulation of metals. Agrostis capillaris accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 0 publications
3
35
1
1
Order By: Relevance
“…For 2-6% SLO in soil, the highest concentration of Pb in tissue was obtained in leaves (Figure 3). This was contrary to reports by Pichtel et al, (2000) and Pichtel and Salt (1998). The data obtained in this study showed that at SLO concentration greater than 1%, there was translocation of Pb from the roots to the leaves.…”
Section: Metal Concentrations In Plant Tissuescontrasting
confidence: 99%
“…For 2-6% SLO in soil, the highest concentration of Pb in tissue was obtained in leaves (Figure 3). This was contrary to reports by Pichtel et al, (2000) and Pichtel and Salt (1998). The data obtained in this study showed that at SLO concentration greater than 1%, there was translocation of Pb from the roots to the leaves.…”
Section: Metal Concentrations In Plant Tissuescontrasting
confidence: 99%
“…An important part of China's sus-tainable development strategy is the ecological restoration of contaminated soils, especially those contaminated by mine tailings (Gao et al 1998), and re-vegetation is a key measure in this restoration (TordoV et al 2000;Wong 2003). However, plant establishment and growth in metal-contaminated sites are inhibited by adverse soil factors, such as acidity, poor physical structure, toxic metals, and nutrient deWciencies (Pichtel and Salt 1998;Wong 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A good vegetation cover is beneficial in the restoration of contaminated land and results in enhanced amenity values as well as prevention of surface soil erosion (Baker et al, 1994). However, adverse factors such as acidity, nutrient deficiencies, toxic heavy metal ions, and poor physical structure, and their interactions of most mine tailings inhibit plant establishment and growth on the tailings (Pichtel and Salt, 1998). The toxicity of heavy metals and deficiency of major nutrients are often the limiting factors for plant establishment on mine tailings, therefore, the success of reclamation schemes should overcome the two major problems (Bradshaw, 1987).…”
mentioning
confidence: 99%